Functional results of minimally invasive cheap fixation technique for all types of intertrochanteric femoral fractures using enders nail and cannulated cancellous screws - Aziz, Ansari Muqtadeer A.; Patel, Altamash A.; Rathod, Pratik P. (International Journal of Research in Orthopaedics, 2022)
Background: The objective was to study functional results of fixation of intertrochanteric fractures of femur using enders nail and cannulated cancellous screws. Methods: This was a prospective observational study. The study was conducted on 30 patients of intertrochanteric femoral fractures who underwent fixation by enders nailing and cannulated cancellous screws in Department of Orthopaedics, GMCH, Aurangabad from January 2018 to January 2021. Patients were assessed functionally using Harris hip score, visual analogue score, and radiological assessment at 3, 6, and 12 months. Results: All patients showed radiological union within 3 months. Functional assessment was done with Visual analogue scale (VAS) in which mean VAS score was 0.9 (range 0-3), mean Harris hip score which was 86 (range 81-90). One patient developed superficial infection at incision site which was treated by giving appropriate antibiotics and one patient complained of prominent nail on medial side of knee which was treated by implant removal after union of fracture. Conclusions: Fixation of intertrochanteric femur fractures using enders nailing and cannulated cancellous screws achieves good stability with minimal complications and improved patients’ outcome in terms of less intraoperative blood loss, less chances of infection, less operative time with minimal patient morbidity and good functional outcome.